ANALYSIS OF THE APPLICATION OF CONSTRUCTION SERVICE INCOME TAX ON PT. CAHAYA SUTRACO PANGKALAN SUSU - Wulandari, Sri Rizki; Fachruddin, Wan; Rizkina, Miftha (Proceeding International Conference of Science Technology and Social Humanities; Vol 1 (2022): International Conference of Science Technology and Social Humanities, 2022)
This research is entitled "Analysis of the Application of Construction Services Income Tax at PT Cahaya Sutraco Pangkalan Susu". This study aims to determine the nature of the imposition and rates of construction services in the Final Income Tax and also to determine whether the application of construction services income tax at PT. Cahaya Sutraco is in accordance with the applicable tax law. The type of research used in thisresearch isdescriptive qualitative research. Data collection techniques in this study are interviews and documentation, and the data used are primarydata and secondarydata. The results of the research that has been done that PT Cahaya Sutraco there is a mistake in calculating the final income tax in the tax base. Employees in the accounting / tax section should be more careful about the calculation of the basis for the imposition of final income tax so that no errors occur in the future.